Mutation in ribosomal protein S5 leads to spectinomycin resistance in Neisseria gonorrhoeae - Ilina, Elena; Malakhova, Maja; Bodoev, Ivan; Filimonova, Alla; Oparina, Nina; Govorun, Vadim (Frontiers in Microbiology, 2013)
Spectinomycin remains a useful reserve option for therapy of gonorrhea. The emergence of multidrug-resistant Neisseria gonorrhoeae strains with decreased susceptibility to cefixime and to ceftriaxone makes it the only medicine still effective for treatment of gonorrhea infection in analogous cases. However, adoption of spectinomycin as a routinely used drug of choice was soon followed by reports of spectinomycin resistance. The main molecular mechanism of spectinomycin resistance in N. gonorrhoeae was C1192T substitution in 16S rRNA genes. Here we reported a Thr-24→Pro mutation in ribosomal protein S5 found in spectinomycin resistant clinical N. gonorrhoeae strain, which carried no changes in 16S rRNA. In a series of experiments, the transfer of rpsE gene allele encoding the mutant ribosomal protein S5 to the recipient N. gonorrhoeae strains was analyzed. The relatively high rate of transformation (ca. 10-5 CFUs) indicates the possibility of spread of spectinonycin resistance within gonococcal population due to the horizontal gene transfer.